Retest and treat: a review of national HIV retesting guidelines to inform elimination of mother‐to‐child HIV transmission (EMTCT) efforts. Issue 4 (8th April 2019) - Drake, Alison L; Thomson, Kerry A; Quinn, Caitlin; Newman Owiredu, Morkor; Nuwagira, Innocent B; Chitembo, Lastone; Essajee, Shaffiq; Baggaley, Rachel; Johnson, Cheryl C
Abstract: Introduction: High maternal HIV incidence contributes substantially to mother‐to‐child HIV transmission (MTCT) in some settings. Since 2006, HIV retesting during the third trimester and breastfeeding has been recommended by the World Health Organization in higher prevalence (≥5%) settings to reduce MTCT. However, many countries lack clarity on when and how often to retest pregnant and postpartum women to optimize resources and service delivery. We reviewed and characterized national guidelines on maternal retesting based on timing and frequency. Methods: We identified 52 countries to represent variations in HIV prevalence, geography, and MTCT priority and searched available national MTCT, HIV testing and HIV treatment policies published between 2007 and 2017 for recommendations on retesting during pregnancy, labour/delivery and postpartum. Recommended retesting frequency and timing was extracted. Country HIV prevalence was classified as: very low (<1%), low (1% to 5%), intermediate (>5 to <15%) and high (≥15%). Women with unknown HIV status at delivery/postpartum were included in retesting guidelines. Results and discussion: Overall, policies from 49 countries were identified; 51% from 2015 or later and most (n = 25) were from Africa. Four countries were high HIV prevalence, seven intermediate, sixteen low and twenty‐two very low. Most (n = 31) had guidance on universal voluntary opt‐out HIV testing at the first antenatal care (ANC) visit. Beyond the first ANC visit, the majority (78%, n = 38) had guidance on retesting; 22 recommended retesting all women with unknown/negative status, five only if unknown HIV status, three in pregnancy based on risk and eight combining these approaches. Retesting was universally recommended during pregnancy, labour/delivery, and postpartum for all high prevalence settings and four of seven intermediate prevalence settings. Five UNAIDS priority countries for EMTCT with low/very low HIV prevalence, but high/intermediate MTCT, had no guidance on retesting. Conclusions: Retesting guidelines for pregnant and postpartum women were ubiquitous in high prevalence countries and defined in some intermediate prevalence countries, but absent in some low HIV prevalence countries with high MTCT. Countries may require additional guidance on how to optimize maternal HIV testing and whether to prioritize retesting efforts or discontinue universal retesting based on HIV incidence. Research is needed to assess country‐level guideline implementation and impact.